Serum Inflammatory Markers in Obstructive Sleep Apnea: A Meta-Analysis - Nadeem, Rashid; Molnar, Janos; Madbouly, Essam M.; Nida, Mahwish; Aggarwal, Saurabh; Sajid, Hassan; Naseem, Jawed; Loomba, Rohit (Journal of clinical sleep medicine, 2013)
Obstructive sleep apnea (OSA) has been linked to and is associated with increased cardiovascular and cerebrovascular morbidity. Ongoing inflammatory responses play an important role in this association. Multiple small size studies addressing the profile of the inflammatory markers in OSA are available therefore we performed a meta-analysis. Systematic review of medical literature was conducted using PubMed, Cochrane, and EMBASE databases from 1968 to 2011 by utilizing the key words obstructive sleep apnea, C-Reactive protein, tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), interleukin 8 (IL-8), intercellular adhesion molecule (ICAM), vascular cell adhesion molecule (VCAM) and Selectins. Inclusion criteria were: full text English articles; studies with adult population; reported values for at least one of the markers of interest; with at least two separate groups (subjects with OSA and control group); OSA was defined as AHI of ≥ 5/h. Five hundred and twelve studies were reviewed for inclusion with 51 studies pooled for analysis (30 studies for CRP, 19 studies for TNF-α, 8 studies for ICAM, 18 studies for IL-6, six studies for VCAM and 5 studies for Selectins). The levels of inflammatory markers were higher in patients with OSA compared to control group. Standardized pooled Mean differences were calculated to be 1.77 for CRP, 1.03 for TNF-α, 2.16 for IL-6, 4.22 for IL-8, 2.93 for ICAM, 1.45 for Selectins and 2.08 for VCAM. In this meta-analysis, the levels of systemic inflammatory markers were found to be higher in OSA patients compared to control subjects.